2021
DOI: 10.1021/acsami.1c00556
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Uranium Adsorption Magnetic Platform Based on Amidoxime-Functionalized Flower-like Fe3O4@TiO2 Core–Shell Microspheres

Abstract: Efficient removal of uranium (U) from aqueous solutions is crucial for ecological safety. Functionalized magnetic nanoparticles provide a promising strategy for radionuclide recovery and separation. However, designing and synthesizing magnetic adsorbents with high sorption capacity and selectivity, accompanied by excellent stability and reusability, remain a challenge. In this work, novel amidoximefunctionalized flower-like magnetic Fe 3 O 4 @TiO 2 core−shell microspheres are designed and synthesized to effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(31 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…The IAA-CTSA exhibited the highest adsorption capacity comparable to most of these alternative adsorbents. 4,28,29,37,57,[61][62][63][64][65][66][67][68][69] Particularly, the maximum adsorp-tion capacity (847.5 mg g −1 ) was dramatically higher than these selected CTS-based adsorbents. 4,28,29,57,[61][62][63][64][65][66][67][68][69] These results revealed the exceptional capture ability of U(VI) on IAA-CTSA benefitting from the synergy of electrostatic interactions, complexation and cation-π interactions.…”
Section: Polymer Chemistry Papermentioning
confidence: 92%
See 1 more Smart Citation
“…The IAA-CTSA exhibited the highest adsorption capacity comparable to most of these alternative adsorbents. 4,28,29,37,57,[61][62][63][64][65][66][67][68][69] Particularly, the maximum adsorp-tion capacity (847.5 mg g −1 ) was dramatically higher than these selected CTS-based adsorbents. 4,28,29,57,[61][62][63][64][65][66][67][68][69] These results revealed the exceptional capture ability of U(VI) on IAA-CTSA benefitting from the synergy of electrostatic interactions, complexation and cation-π interactions.…”
Section: Polymer Chemistry Papermentioning
confidence: 92%
“…4,28,29,37,57,[61][62][63][64][65][66][67][68][69] Particularly, the maximum adsorp-tion capacity (847.5 mg g −1 ) was dramatically higher than these selected CTS-based adsorbents. 4,28,29,57,[61][62][63][64][65][66][67][68][69] These results revealed the exceptional capture ability of U(VI) on IAA-CTSA benefitting from the synergy of electrostatic interactions, complexation and cation-π interactions. Thus, IAA-CTSA is an applicable, environmentally friendly and costeffective candidate for extraction, pretreatment and recovery of U(VI) in aqueous solution.…”
Section: Polymer Chemistry Papermentioning
confidence: 92%
“…Recently, silica, apart from serving as a protection layer or functionalization bridge, has also been used as a hard template for the crystallization of titanium oxide-based nanosheets. Zhao et al [ 126 ] synthesized amorphous TiO 2 on silica–Fe 3 O 4 , using the Stöber method. Then, the silica layer was removed by dissolution in a strong alkali solution, followed by recrystallization of the H 2 Ti 2 O 5 nanosheet, by redissolving TiO 2 in diluted hydrochloric acid.…”
Section: Conventional Synthesis Methods Of Magnetic Adsorbentsmentioning
confidence: 99%
“…Xu et al first reported a kind of groundbreaking 3D hierarchical porous AO adsorbents via multi-step grafting polymerization which achieved a high capacity of 11.50 mg·g –1 after trimestral successive adsorption in natural seawater . Recently, a novel functionalized magnetic Fe 3 O 4 @TiO 2 core-shell microspheres were designed by Zhao et al via classical solvent hydrothermal method exhibited the maximum uranium adsorption capacity of 313.6 mg·g –1 at pH 6.0 . For uranium extraction from high salinity seawater, an outstanding investigation has reported a photoelectric-assisted method by exploiting a kind of bifunctional nitride material.…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, a novel functionalized magnetic Fe 3 O 4 @TiO 2 core-shell microspheres were designed by Zhao et al via classical solvent hydrothermal method exhibited the maximum uranium adsorption capacity of 313.6 mg•g −1 at pH 6.0. 20 For uranium extraction from high salinity seawater, an outstanding investigation has reported a photoelectric-assisted method by exploiting a kind of bifunctional nitride material. The result indicated that the extraction capacity of the adsorbent could be significantly improved to reach 1556 mg• g −1 under light illumination.…”
Section: Introductionmentioning
confidence: 99%